Aktivisme Digital dan Demokrasi di Indonesia: Menegakkan Hak-Hak Konstitusional Warga Negara Dalam Kontitusionalisme Digital - Indra Budi Jaya (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
The development of digital technology has shifted people's mindsets and brought about significant changes in democratic practices in Indonesia. Public activity spaces are now no longer limited to conventional spaces, but rather digital spaces, which have become new arenas for every citizen to freely express opinions, conduct oversight, and disseminate information as part of their digital rights. However, the discourse on democracy in the digital era raises serious challenges to the enforcement and protection of constitutional rights, which have subsequently transformed into digital constitutionalism. The background to this problem encourages the importance of discussing digital activism and its relevance to digital democracy, as well as how the government upholds citizens' constitutional rights within the framework of digital constitutionalism in Indonesia. The problem formulation in this paper is: First, How is digital activism and digital democracy in Indonesia? Second, the digital constitutional framework and its implementation on citizens' rights in Indonesia. The analytical method used in this study is normative juridical research with a conceptual approach and a statutory approach. The results of the analysis show that digital activism has become a new space for political participation and public control that creates a digital society (digital citizenship). However, digital activism should not be reduced to mere techno-determinism, considering the shadow of pseudo-participation often follows digital activism. The digital constitutional framework actually starts from constitutional rights guaranteed through the Constitution and other implementing regulations. Adaptation of technological applications has shifted the concept of human rights to be broader, such as the right to data privacy, the right to express oneself on the Internet, and the right to obtain information.